Faktor - Faktor Yang Mempengaruhi Konsumsi Gula Pasir di Indonesia - Satriana, Eka Dewi; Tety, Ermi; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research are: (a) to know the development of Indonesia’s sugar consumption aggregately during 1980-2011 (b) to analyze the factors that affecting on production, consumption, and domestic price of sugar in Indonesia (c) to analyze the changing’s influence of exogenous factor on endogenous factor. The data that used is time series data of 1992-2011 obtained from various source such as BPS, DGI, Ditjen Perkebunan etc. the analysis method that used is 2SLS method with simultaneous model. The result of this research shows that the development of sugar’s consumption aggregate in Indonesia during 1980-2011 has been increasing from year to year. However, the increasing of sugar’s consumption haven’t comparable yet with the increasing of domestic sugar’s production. Sugar’s production significantly affected by sugar cane’s plantation area and coffee’s price as complement product. Direct consumption of sugar significantly affected by civilization’s quantity and the consumption’s a year before. While the domestic price significantly affected by world’s price, the exchange value of Rupiah and the price a year before. The increasing of capita’s income affecting on increasing of direct consumption, the production and domestic price of sugar. The increasing of world’s sugar price affecting on the increasing of sugar’s production and domestic price while the consumption of sugar is decreasing. The increasing of Rupiah’s value affecting on decreasing of consumption, increasing domestic price of sugar , and increasing of sugar’s production. The increasing of sugar’s import value affecting on decreasing of domestic sugar’s production, while the consumption of sugar is increasing because of the domestic’s price is decreasing. Key words : Consumption, Production, Domestic Price, Sugar.